(untitled) (SciELO Preprints, 2022)
Introduction: The mandibular canal (MC), located within the mandible, carries the inferior alveolar nerve and the inferior alveolar vessels. This neurovascular bundle is at risk during mandibular surgical procedures. Therefore, an adequate preoperatively evaluation of the MC could lead to safer treatment with less postoperative complications. Aim: The aim of this paper was to review the most common radiographic techniques of the MC for better preoperative planning in dentistry. Methods: Three radiographic techniques (periapical, panoramic and cone-beam computed tomography) along with their advantages and disadvantages are hereby reviewed with special emphasis on their clinical applicability in the dentist’s everyday practice. Discussion: Panoramic radiography and cone-beam computed tomography technology are considered very useful in the assessment of the MC. Conclusion: All techniques reviewed in this paper except the periapical radiography can be useful in the visibility of the MC.